2017
DOI: 10.1097/qai.0000000000001461
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Isoniazid Preventive Therapy Care Cascade Among HIV-Positive Female Sex Workers in Mombasa, Kenya

Abstract: Background Kenyan female sex workers (FSWs) have a high HIV prevalence, increasing their tuberculosis (TB) risk. Despite recommendations that HIV-positive individuals be offered isoniazid preventive therapy (IPT), uptake has been limited. Methods In this longitudinal cohort of HIV-positive FSWs, we retrospectively characterized the IPT care cascade between March 2000–January 2010, including reasons for cascade loss or appropriate exit. Cascade success required completion of 6 months of IPT. Baseline characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 30 publications
4
29
0
1
Order By: Relevance
“…HIV patients with high CD4 counts ≥350 cells/µL had lower prevalence of IPT completion compared with those with CD4 counts <100 cells/µL. This is consistent with studies in Kenya and Brazil (30,37). Possibly patients with high CD4 counts perceive themselves healthy and not at risk of progressing to active TB, so they stop taking IPT before completing the full treatment course of six months.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…HIV patients with high CD4 counts ≥350 cells/µL had lower prevalence of IPT completion compared with those with CD4 counts <100 cells/µL. This is consistent with studies in Kenya and Brazil (30,37). Possibly patients with high CD4 counts perceive themselves healthy and not at risk of progressing to active TB, so they stop taking IPT before completing the full treatment course of six months.…”
Section: Discussionsupporting
confidence: 86%
“…WHO recommends the completion of at least six months IPT for the successful prevention of active tuberculosis among PLHIV (4,10). Globally, six-month IPT completion has been reported to range from 39-99% (28)(29)(30)(31)(32)(33)(34)(35)(36)(37), and in Tanzania studies reported 65%-98% of those who initiated IPT, completed the six month treatment course (6,20,(38)(39)(40). Most epidemiological studies have shown that IPT completion reduces the risks of mortality among PLHIV (8,26,41), decreases the need for expensive TB treatment needs and lowers the cost of HIV services.…”
Section: Introductionmentioning
confidence: 99%
“…Though our study was focusing on only those on ART, we do not think this differs much as the country's policy has been the initiation of IPT regardless of ART status. Kenya adopted routine TB screening for PLHIV at every clinic visit by use of the ICF tool in 2011 [20,25] to accommodate for pediatrics and Adults. This has recently been reinforced…”
Section: Discussionmentioning
confidence: 99%
“…WHO recommends the completion of at least six months IPT for the successful prevention of active tuberculosis among PLHIV (4,10). Globally, six-month IPT completion has been reported to range from 39-99% (28)(29)(30)(31)(32)(33)(34)(35)(36)(37), and in Tanzania studies reported 65%-98% of those who initiated IPT, completed the six month treatment course (6,20,(38)(39)(40). Most epidemiological studies have shown that IPT completion reduces the risks of mortality among PLHIV (8,26,41)…”
Section: Introductionmentioning
confidence: 99%